105k views
1 vote
Please answer!! I tried doing it myself and it didn’t work. Again pls answer! Rewards are 20 points

Please answer!! I tried doing it myself and it didn’t work. Again pls answer! Rewards-example-1

2 Answers

5 votes

Answer:


y = - 45

Explanation:


(y)/(3) + 6 = - 9


(y)/(3) + 6 \: - 6 = - 9 - 6


3 * (y)/(3) = - 15 * 3


y = - 15 * 3


y = - 45

User Foo Bah
by
4.3k points
2 votes

Answer:-45

Step-by-step explanation:this is how I do it: draw a line in the middle of the equal sign. Now its split in two parts. Do the opposite operation on the left side, so minus 6 from the left AND the right. Now it equals to y/3 = -15. Now times each side by 3 so the y stands alone. -15 times 3 equals -45. Y = -45. Sorry it's kinda hard to explain!

User Abdullah Al Shakib
by
4.9k points